2019
DOI: 10.3390/ijms20030459
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Inflammation: Proof of Concept Based on Two Illustrative Cytokines

Abstract: Obstructive sleep apnea syndrome (OSAS) is a markedly prevalent condition across the lifespan, particularly in overweight and obese individuals, which has been associated with an independent risk for neurocognitive, behavioral, and mood problems as well as cardiovascular and metabolic morbidities, ultimately fostering increases in overall mortality rates. In adult patients, excessive daytime sleepiness (EDS) is the most frequent symptom leading to clinical referral for evaluation and treatment, but classic EDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
156
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(192 citation statements)
references
References 174 publications
3
156
1
8
Order By: Relevance
“…Previous studies have shown that plasma pro-inflammatory cytokines, such as high density-CRP (HS-CRP), TNF-α, IL-1β, IL-6, and IL-10, were elevated in children with OSA. Besides, the expression ratio of IL-10 and TNF-α was not normalized even after adenotonsillectomy [12]. In our previous study, we reported that HS-CRP, IL-17, and IL-23 were elevated in children with OSA compared with healthy controls [11] and that most of them had tonsil or adenoid hypertrophy.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have shown that plasma pro-inflammatory cytokines, such as high density-CRP (HS-CRP), TNF-α, IL-1β, IL-6, and IL-10, were elevated in children with OSA. Besides, the expression ratio of IL-10 and TNF-α was not normalized even after adenotonsillectomy [12]. In our previous study, we reported that HS-CRP, IL-17, and IL-23 were elevated in children with OSA compared with healthy controls [11] and that most of them had tonsil or adenoid hypertrophy.…”
Section: Introductionmentioning
confidence: 84%
“…and Interferon-γ (IFN-γ) are related to pediatric OSA. A recent review article showed that plasma IL-6 level was significantly reduced after adenotonsillectomy (T&A) in patients with pediatric OSA, especially those with obesity [12]. However, the results of previous studies are still ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings support that patients with OSAS have higher pro-in ammatory cytokine basal levels. OSAS in both adults and children has been found to promote a persistently low-intensity in ammatory state, expressed by IL-6 [9]. The concentration of IL-6 has been comprehensively evaluated as a contributor to the regulation of sleep in brain areas such as the hypothalamus and hippocampus [16].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been demonstrated that increases in in ammatory markers in OSAS patients likely re ect the presence of underlying silent or overt end-organ morbidity [9]. IL-6 induces oxidative stress and promotes NF-κB-dependent endothelial dysfunction [24,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation